Business Strategy Analysis via Instagram @Laukita Using the Peso Approach - T, Mirakel Alantaurizqa; N.Z, Ratu Devindha; G, Jessrine Greivin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Branding is a marketing strategy that aims to communicate messages from a business to consumers. Laukita is here by bringing branding to people's minds with a fast food theme that is different from competitors in terms of presentation and the menu variants they offer. The aim of this research was to understand and analyze the branding strategy used by Laukita in the Covid-19 pandemic era, especially through social media. Researchers use the Social Media theory put forward by Nasrullah, with the PESO concept model from Gini Dietrich. The research method in this study used a descriptive qualitative type. The data used in this research was primary data obtained from interviews with sources and secondary data obtained through literature study. The results of the research showed that paid media elements have an important role in the Laukita branding development process, then earned media elements using reviewers and influencers, supported by shared media elements that use Laukita's social media, and owned media elements that manage all Laukita media channels so that they can Do strong branding in the minds of consumers